Using Shadow Page Cache to Improve Isolated Drivers Performance - Hao Zheng; Xiaoshe Dong; Endong Wang; Baoke Chen; Zhengdong Zhu; Chengzhe Liu (The Scientific World Journal)
With the advantage of the reusability property of the virtualization technology, users can reuse various types and versions of existing operating systems and drivers in a virtual machine, so as to customize their application environment. In order to prevent users’ virtualization environments being impacted by driver faults in virtual machine, Chariot examines the correctness of driver’s write operations by the method of combining a driver’s write operation capture and a driver’s private access control table. However, this method needs to keep the write permission of shadow page table as read-only, so as to capture isolated driver’s write operations through page faults, which adversely affect the performance of the driver. Based on delaying setting frequently used shadow pages’ write permissions to read-only, this paper proposes an algorithm using shadow page cache to improve the performance of isolated drivers and carefully study the relationship between the performance of drivers and the size of shadow page cache. Experimental results show that, through the shadow page cache, the performance of isolated drivers can be greatly improved without impacting Chariot’s reliability too much.